A competência em informação no desenvolvimento didático-pedagógico dos docentes bacharéis no ensino superior - Lima, Brena Menezes (2024)
The research aims to analyze the development of information skills aimed at the didactic-pedagogical performance of teachers who have initial training in bachelor's degrees. The study was carried out at the Faculdade Metropolitana de Horizonte (FMH), located in the city Horizonte, Metropolitan Region of Fortaleza, Ceará. In this context, its specific objectives are: Investigate teacher’s perception of information literacy in the educational context; Identify the informational needs for the professional performance of teachers with a bachelor’s degree in undergraduate courses; Assess the congruence between the principles of information literacy and the educational practices adopted by bachelor's teachers. This is a qualitative research, exploratory in nature, being carried out through a bibliographical review to achieve theoretical support on the topic addressed. As a data collection instrument, questionnaires were applied to teachers who had initial training (undergraduate) in bachelor's or technologist courses who are part of the teaching staff at Faculdade Metropolitana de Horizonte in the semester 2024.1. It can be concluded that the research presented the intersection between Information Competence and pedagogical practices, revealing the informational needs of bachelor's teachers and the importance of CoInfo for professional and academic development, benefiting not only the teacher, but also students through training them to competently exercise their role in society.